Impact of National HIV and AIDS Communication Campaigns in South Africa to Reduce HIV Risk Behaviour - Karl Peltzer; Warren Parker; Musawenkosi Mabaso; Elias Makonko; Khangelani Zuma; Shandir Ramlagan (The Scientific World Journal)
In South Africa social and behavioural communication interventions are a critical component of HIV/AIDS prevention, and numerous communication campaigns have been implemented intensively across the country through government initiatives and nongovernmental organisations over the past decade. The aim of this paper is to assess the reach of HIV and AIDS communication campaigns in conjunction with contributions to knowledge, attitudes, and HIV risk behaviours in the general population in South Africa. The sample included in this nationally representative cross-sectional survey was 13234 people aged 15–55 years. Overall, the study found that there was high exposure to 18 different HIV communication programmes (median 6 programmes and 14 programmes more than 30%) across different age groups. Most programmes were more often seen or heard by young people aged between 15 and 24 years. In multivariate analysis, greater exposure to HIV mass communication programmes was associated with greater HIV knowledge, condom use at last sex, having tested for HIV in the past 12 months, and less stigmatizing attitude toward PLWHA.